Cognitive narrative psychotherapy : research foundations - Gonçalves, Óscar F. (1999)
There has been an increased interest in the study of language processes in psychotherapy. More recently, research and theoretical formulations of the therapeutic process suggested that we must move from the microscopic study of verbal modes to a macroscopic approach in which these modes are organized into narratives. Narratives are conceived, in this perspective, as the basic instruments for meaning making. In this article the research on narrative processes in psychotherapy is reviewed and discussed in terms of its implications for the theory and practice of cognitive narrative psychotherapy. Additionally some of the main data coming from research projects on cognitive narrative psychotherapy are presented.